Analisis Konten Pada Akun Tiktok @Indrasugiarto Sebagai Media Edukasi Anti Manipulasi Pada Korban Narsistik - Firdayanti, Husna; Zainal Abidin; Rastri Kusumaningrum (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The purpose of this study is to describe the main themes presented in the anti-manipulation educational content on the TikTok account @indrasugiarto. Analyze the communication strategies and message delivery styles used by the TikTok account @indrasugiarto in educating its audience. Identify the potential educational impact of the TikTok account content @indrasugiarto on the understanding and awareness of anti-manipulation in narcissistic victims. This research method uses a qualitative approach with a content analysis design. Data collection techniques in this study focus on systematic documentation and recording of research objects including systematic observation, recording (Download) Content. Verbal Content transcription and recording data and Context. The data collection and analysis process will be carried out independently by researchers with internet access. The results of the study state that the TikTok account @indrasugiarto implements an effective and adaptive digital communication strategy, by optimally utilizing platform features to convey mental health education in a straightforward and easy-to-understand manner. This approach not only strengthens the role of the account as a credible influencer, but also has significant potential in increasing understanding, awareness, and empowerment of the audience, especially narcissistic victims. Drawing on communication and learning theories, this account successfully combines digital education with positive social impact in the new media space